PENGARUH BELANJA FUNGSI PENDIDIKAN PEMERINTAH DAERAH TERHADAP KUALITAS SDM DAERAH TERTINGGAL - Adhi Prasetyo; Marihot Nasution (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2017)
The commitment of the Indonesian government in improving education is done by allocating education expenditure at least 20 percent from APBN and APBD. Although it has been in effect since 2003, this commitment needs to be evaluated from the perspective of human resource quality improvement, especially in underdeveloped areas. Underdeveloped areas are preferred because these areas are less developed than other regions. These areas have high poverty incidence, low economic development, and low quality of resurces.This study examines the impact of education spending on the quality of human resources in remote areas as measured by net enrollment rates and the average length of schooling/mean year school by 2015. The results show that the increase of education spending has not been able to improve the quality of human resources in remote areas. The allocation of education spending that is not in line with the number of people in disadvantaged areas has been pointed out as one indication that the utilization of education spending has not been optimal to achieve better quality of human resources.